Impact of FACTS Devices in Optimal Generation in Deregulated Power System - Gouda, Pramod Kumar; Hota, Prakash Kumar (International Journal of Applied Power Engineering (IJAPE), 2015)
Since Gencos and Discos compete primarily based on the price in a deregulated market, minimizing the losses or regulating the voltage or controlling the power flow within the rating of power system components such as cables, transformers, transmission lines become extremely difficult. Recent developments in FACTS devices increases the number of constraints and nonlinearity, and henceachieving the optimal solution becomes further complicated. The Optimal Power Flow Problem, determines the best way to operate a power system at any given instant. It solves the power system load flow with an aim to optimize system operating conditions while automatically adjusting control variable settings without violating the system operating constraints. In this paper such constraints based OPF scheme is developed and presented which also incorporates various Flexible AC Transmission Devices. In this work three different types of FACTS devices namely SVC, TCSC, UPFC are separately included into the OPF problem in addition to the conventional constraints that govern an OPF solution. An IEEE 30 bus system is considered and the results obtained for three different loading conditions with three different FACTS devices and their performance are evaluated.